The fight against tuberculosis in Peru at present - Paz Soldán, Carlos Enrique (1929)
Since we occupy the Chair of Hygiene, Faculty of Medicine, Lima, in 1920, it has been our constant concern awaken in students enthusiasm for this discipline. Rather than direct our teaching towards preparing exams, our work has aimed to show students, our work is aimed at showing students the infinite horizons virgin almost all methodical exploration technique, which provides, among us, Hygiene.